J-TAIL-2: A Prospective, Observational Study of Atezolizumab Combined With Carboplatin and Etoposide in Patients With Extensive-Stage SCLC in Japan - Eisaku Miyauchi, MD, PhD; Makoto Nishio, MD, PhD; Kadoaki Ohashi, MD, PhD; Atsushi Osoegawa, MD, PhD; Eiki Kikuchi, MD, PhD; Hideharu Kimura, MD, PhD; Yasushi Goto, MD, PhD; Junichi Shimizu, MD, PhD; Hiroshige Yoshioka, MD, PhD; Ichiro Yoshino, MD, PhD; Toshihiro Misumi, PhD; Nobuyuki Katakami, MD, PhD; et al. (JTO Clinical and Research Reports)
Introduction: On the basis of the IMpower133 trial, atezolizumab plus carboplatin and etoposide (CE) is approved as first-line treatment for extensive-stage (ES)-SCLC. The J-TAIL-2 study evaluated atezolizumab plus CE in routine clinical practice settings. Methods: J-TAIL-2 was a prospective, multicenter observational study in Japan. Patients with ES-SCLC received atezolizumab plus CE in clinical practice. The primary end point was 12-month OS rate. Secondary end points included overall survival (OS), progression-free survival (PFS), and safety in select subgroups, including the IMpower133-unlike (i.e., Eastern Cooperative Oncology Group performance status 2 or more, interstitial lung disease, autoimmune disease) versus IMpower133-like groups. Results: Overall, 403 patients were included; the median age was 71 years, 16.6% (n = 67) had an Eastern Cooperative Oncology Group performance status 2 or more, 26.8% (n = 108) had brain metastasis, 6.9% (n = 28) had interstitial lung disease, 4.0% (n = 16) had autoimmune disease, and 72.7% (n = 293) were IMpower133-unlike. In the efficacy population (n = 399), the 12-month OS rate was 63.7%, median OS was 16.5 months, and median PFS was 5.1 months. In IMpower133-unlike versus IMpower133-like subgroups, the 12-month OS rate was 58.5% versus 77.5%, median OS was 15.5 versus 19.1 months (hazard ratio, 1.32; 95% confidence interval: 0.98–1.77), and median PFS was 4.8 versus 5.4 months (hazard ratio, 1.14; 95% confidence interval: 0.90–1.45). No new safety signals were observed (safety population, n = 400); safety outcomes in the IMpower133-unlike and IMpower133-like subgroups were similar. Conclusions: In J-TAIL-2, atezolizumab plus CE had efficacy in patients with ES-SCLC in clinical practice that was consistent with that in IMpower133. Taken together with the acceptable safety profile, these data support the use of atezolizumab plus CE in patients with ES-SCLC in Japan, including those who would have been ineligible for IMpower133.